Manfaat Bahan dan Pupuk Organik pada Tanaman Padi di Lahan Sawah Irigasi - Suyamto Suyamto (Iptek Tanaman Pangan, 2017)
If there is a negative impact of the implementation of Green Revolution it is an excessive usages of chemical fertilizers and minimum uses of organic fertilizers, practiced by rice’s farmers. The government had supported the use of organic fertilizer by subsidizing the price of organic fertilizer. However, farmers did not interested in applying organic fertilizers, for reason that application of organic fertilizer is more cumbersome and the effect on crop yield is not readily visible, if compared with that of applying chemical fertilizers. The objective of this paper was to review the benefit of organic matter as fertilizer applied on irrigated rice land. It had been known that organic matter play important roles in improving physical, chemical and biological soil fertility, as well as a source of nutrients for crop plants. Those roles would be more significant in dry lands, but it would be less significant in the lowland irrigated rice soils. Soil preparation broke the soil structure, soil permeability and improved water holding capacity. The submerged soil tended to buffer soil pH into neutral, that caused all nutrients became more available for crop. Submerged soil also made soil unaerobic that would slow the rate of organic matter decomposition. It meant that the benefit of organic matter as fertilizer for improving physical, chemical and biological fertility was slow. The benefit of organic matter as fertilizers for rice on submerged soil was as a source of essential macro nutrients. However, the content in the organic fertilizer would not match with the nutrients taken up or removed by the crop. Therefore, applying of only organic fertilizers alone could not meet with the requirement of NPK nutrients for rice, rather it would be more advantageous to combine both organic and chemical fertilizers. The use of matured organic fertilizers with the C/N ratio of <15 was suggested.